Cognitive skill attainment and its relationship to the skill of crushing volleyball among students of the fourth stage of the College of Physical Education and Sports Sciences for Girls - دنيا اسعد عبود أ.م. د نعيمة خلف زيدان (الرياضة المعاصرة)
has reached the importance of skill knowledge in the performance of volleyball skills, especially the overwhelming hitting skill, as the research aims to identify the relationship of skill cognitive achievement and its relationship to the overwhelming hitting skill among students of the fourth stage - College of Physical Education and Sports Science for Girls - Kirkuk, and the descriptive approach has been used The number of the sample was (25) female students divided (5) sample from the exploratory experience and (20) female students from the main experiment sample. The results showed that there is a relationship of skill cognitive achievement and its relationship to skill for overwhelming hitting skill with volleyball.